The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/app.45854
|View full text |Cite
|
Sign up to set email alerts
|

Fouling evaluation of polyethersulfone (PES)/sulfonated cation exchange resin (SCER) membrane for BSA separation

Abstract: In this study, antifouling membranes were prepared through dry wet‐phase inversion method. The incorporation of electrostatistically charged group of sulfonate cation exchange resins (SCER) into polyethersulfone membrane matrix attempts to give a synergistic combination of properties for bovine serum albumin (BSA) removal. The effect of different composition of SCER into the blend membranes were characterized using scanning electron microscopy, atomic force microscopy, porosimeter, attenuated total reflectance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The magnitudes of flux can be improved by decreasing membrane thickness. The selectivity of PVDF HPMs has been assessed by filtrating BSA solution [ 33 , 34 , 35 , 36 , 37 ]. As shown in Figure 6 B, the specimens from 1–10, 1–20, 2–10 and 2–20 exhibit a rejection ratio of ~80%.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitudes of flux can be improved by decreasing membrane thickness. The selectivity of PVDF HPMs has been assessed by filtrating BSA solution [ 33 , 34 , 35 , 36 , 37 ]. As shown in Figure 6 B, the specimens from 1–10, 1–20, 2–10 and 2–20 exhibit a rejection ratio of ~80%.…”
Section: Resultsmentioning
confidence: 99%
“…The pure and PVDF‐B 4 C photocatalytic membranes using the phase inversion 23,24 . In brief, a predetermined amount of B 4 C nanoparticle (NP) was dispersed in DMAC using the probe ultrasonicator (KS‐250SDN) for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…The pure and PVDF-B 4 C photocatalytic membranes using the phase inversion. 23,24 In brief, a predetermined amount of B 4 C nanoparticle (NP) was dispersed in DMAC using the probe ultrasonicator (KS-250SDN) for 15 min. Then, PVDF powder was added into the dispersed solution under agitation of 350 rpm for 16 h. For pure membrane, PVDF powder was added in DMAC under agitation of 350 rpm for 16 h. Table 1 presents the composition of membrane dope solution.…”
Section: Synthesis Of Pure and Pvdf-b 4 C Mixed Matrix Membranesmentioning
confidence: 99%
“…This is because functionalized membranes form strong bonds with the components and are less vulnerable to heat degradation. Membrane hydrophilicity plays an important role in fouling resistance, and previous research has suggested that organic components such as HA and protein usually exhibit lower fouling tendencies when using a more hydrophilic surface [40,41]. The contact angle of the prepared membranes is shown in Table 3.…”
Section: Membrane Characterizationmentioning
confidence: 99%